Tonal calls as a bioacoustic novelty in two Atlantic Forest species of Physalaemus (Anura: Leptodactylidae) - Carvalho, Thiago R. de [UNESP]; Haddad, Celio F. B. [UNESP]; Gridi-Papp, Marcos (Firenze Univ Press, 2019)
The frog genus Physalaemus has almost 50 species with vocalizations that are mostly composed of a single note. This note tends to have a broad harmonic structure or a pulsed structure. The sister species P. lateristriga and P. olfersii have pulsed advertisement calls that have been described as a noisy and long-lasting warbling sound. We provide the first account of inclusion of tonal sounds as part of the vocal repertoire of these species. Pure tones can (1) be long and form the entire call; (2) form prefixes of variable length separated by silence from the advertisement call; (3) be brief and form the onset or the offset of the regular advertisement call. Tonal calls may be an evolutionary novelty and they are not known from other populations of P. olfersii and P. lateristriga. Identification of the mechanism of sound production and of the behavioural roles of these unique calls may help elucidate the evolution of call complexity in frogs.
Keywords: Animal communication; bioacoustics; Leiuperinae; vocal repertoire